2016
DOI: 10.1016/j.nucengdes.2016.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity studies on the multi-sensor conductivity probe measurement technique for two-phase flows

Abstract: The objective of this study is to advance the local multi-sensor conductivity probe measurement technique through systematic investigation into several practical aspects of a conductivity probe measurement system. Firstly, signal "ghosting" among probe sensors is found to cause artificially high bubble velocity measurements and low interfacial area concentration (a i) measurements that depend on sampling frequency and sensor impedance. A revised electrical circuit is suggested to eliminate this artificial vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Using this frequency for measurements ensures that the quantization error of the statistical results is at least less than 10% of the average value. However, the measurement results are not more accurate as the frequency increases because the signal overlap phenomenon becomes more pronounced at higher measurement frequencies, which significantly impacts the measurement results . Therefore, the highest measurement frequency of the instrument, 20 kHz, was not used in this experiment, but a relatively high accuracy of 10 kHz was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…Using this frequency for measurements ensures that the quantization error of the statistical results is at least less than 10% of the average value. However, the measurement results are not more accurate as the frequency increases because the signal overlap phenomenon becomes more pronounced at higher measurement frequencies, which significantly impacts the measurement results . Therefore, the highest measurement frequency of the instrument, 20 kHz, was not used in this experiment, but a relatively high accuracy of 10 kHz was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…Sampling time and frequency have been validated in Peng et al 13 as well. It is worth noting that Worosz et al 63 found that the interfacial area measurement strongly depends on the selection of the sampling frequency. Only when the sampling frequency is larger than 100 kHz can the measured interfacial area within ±5% of the values at 250 kHz be guaranteed.…”
Section: Dual-tip Conductivity Probesmentioning
confidence: 99%
“…Some invasive detection methods, such as the conductance needle method, have limited application scope because of their interference with the movement of the bubbles in a flow field. 7 In recent years, the rapid development of high-speed photography and digital image processing technology provides new possibilities for noncontact measurements. Based on these techniques, many researchers, such as Mohagheghian and Elbing 8 and Feng et al, 9 have analyzed the bubbly flow characteristics in gas−liquid two-phase flow under different working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As bubbles often appear in clusters in the liquid phase, it is difficult to accurately capture the morphology and size distribution characteristics of bubbles. Some invasive detection methods, such as the conductance needle method, have limited application scope because of their interference with the movement of the bubbles in a flow field . In recent years, the rapid development of high-speed photography and digital image processing technology provides new possibilities for noncontact measurements.…”
Section: Introductionmentioning
confidence: 99%